IoT based smart home automation and energy management - Saha, Subroto; Ishraque, Hasin; Islam, Md. Tawfat-ul; Rahman, Md. Arifur (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.